GENOMIC DETECTION AND EXPRESSION OF ANTIMICROBIALS PEPTIDES (? - AND ? - DEFENSINS) IN INTESTINAL MUCOUS OF NEWBORN ALPACA (VICUGNA PACOS) - More B., Juan (2011)
The aim of this study was to determine the presence of genomic ?-and ? -defensins (bovine enteric beta defensin – ?-def alp – and Defa 8 respectively) and their levels of expression as messenger RNA in samples of intestinal mucosa of newborn alpacas. Samples of jejunum of 30 animals from 0 to 45 days of age were collected. Genomic DNA and mRNA were extracted for PCR analysis and real-time RT-PCR respectively. All samples amplified a single DNA segment (between 800 and 900 pb) by PCR which corresponds to the alpha defensin 8 (defa 8), while 90% (27/30) amplified a segment expected 300-350 pb for ?-def alp and two additional bands of 800-900 pb evidenced by agarose gel electrophoresis. The detection of mRNAs by real time RT-PCR was performed based on Cycle threshold (Ct) analysis and Melting temperature (Tm) of the amplified products. The Cts for defa 8 products were found between 25.1 and 39.5 cycles with an average of 36.4 ± 1.9, and the Tm of the amplicons was located between 79.1 and 85.7 ºC. The Cts for ?-def alp were found between 22.7 and 36.8 cycles with an average of 32.4 ± 3.3 and the Tm of these amplified products ranged between 71 and 81.9 ºC. The expression levels were determined by relative quantification based on the comparative Ct method. The results showed increased levels of defa 8 and ?-def alp until the 3rd week of age, and a decline between the 4th and 6th week of age. The results demonstrate the genomic presence and expression of ? - and ?-defensins in the jejunum of alpacas younger than 45 days old.